2013
DOI: 10.1016/j.neuroimage.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-band suppression in the visual word form area as a functional bottleneck to consciousness

Abstract: The current state of empirical investigations refers to consciousness as an all-or-none phenomenon. However, a recent theoretical account opens up this perspective by proposing a partial level (between nil and full) of conscious perception. In the well-studied case of single-word reading, short-lived exposure can trigger incomplete word-form recognition wherein letters fall short of forming a whole word in one's conscious perception thereby hindering word-meaning access and report. Hence, the processing from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
(82 reference statements)
3
15
0
Order By: Relevance
“…Hence, other neuronal populations could also play a role in morphological unification, although one should also keep in mind that the heavy cognitive load imposed by this paradigm is suggestive of selective language processing occurring only late in time. Similarly in a previous experiment imposing heavy load due to semantic decision at the threshold of visual recognition, we reported specific effects not earlier than 500 ms post stimulus onset [Levy et al, 2013]. Future studies probing unification may reveal such other putative neuronal dynamics.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hence, other neuronal populations could also play a role in morphological unification, although one should also keep in mind that the heavy cognitive load imposed by this paradigm is suggestive of selective language processing occurring only late in time. Similarly in a previous experiment imposing heavy load due to semantic decision at the threshold of visual recognition, we reported specific effects not earlier than 500 ms post stimulus onset [Levy et al, 2013]. Future studies probing unification may reveal such other putative neuronal dynamics.…”
Section: Discussionsupporting
confidence: 84%
“…This is concordant with our previous fMRI study [Levy et al, 2008] which also showed such a response to visual feature analysis in comparison to a pLOT response to orthographic processing. Likewise, late NBR in the motor cortex contralateral to the response press is often observed during tasks implicating motor response [e.g., Donner et al, 2009;Levy et al, 2013], and is, therefore, probably reflecting, in this experiment, the right-hand motor press for the task response. These findings thereby illustrate various neural activities in different time-frequency windows in a broad spectrum of the gamma band, each conveying a different function.…”
Section: Discussionsupporting
confidence: 55%
“…2011). Consistently, Levy et al (2013) found that alphaband suppression in the VWFA mediates conscious word form perception. In addition, Strauß, Kotz, Scharinger, and Obleser (2014) found decreased alpha power over left posterior temporal areas with increased activation of semantic features.…”
Section: Alpha Depression Reflects Engagement Of the Language Networkmentioning
confidence: 63%
“…GPC involves left ventral occipito-temporal cortex (vOTC, also called the “Visual Word Form Area”) which is highly word-like selective (Hamamé et al, 2013; Perrone-Bertolotti et al, 2014) and considered a central node in visual language processing (Dehaene et al, 2005, 2015; Vinckier et al, 2007; Cohen et al, 2008; see also Seghier et al, 2012). This region interacts with high-level language regions (such as the inferior frontal gyrus, Bitan et al, 2005; Vidal et al, 2012; Yvert et al, 2012; Perrone-Bertolotti et al, 2014; Schurz et al, 2014) and is modulated by top-down perceptual processes (Levy et al, 2013; Vidal et al, 2014). The GPC also involves the inferior parietal lobule (iPL) and the supramarginal gyrus (SMG; Jobard et al, 2003; Vigneau et al, 2006; Juphard et al, 2011; see also Stoeckel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%